Phytochemical Variation of Wild and Farmed Populations of Boldo (Peumus Boldus Molina) - Echeverria-Morgado, J (Elsevier GmbH, 2023)
The phytochemical profile of six wild and one cultivated Peumus boldus (boldo) populations from different regions of north-central, central and south-central Chile was studied. In leaves, wood, and bark, alkaloids and phenolics were analyzed by UHPLC-MS-MS and leaf essential oils by GC-MS. In each population, compounds were found to exhibit high variability, but important differences were recorded at the population level. The north-central wild populations showed higher concentrations of alkaloids and polyphenols in leaves and alkaloids in the bark compared to more southern populations. Saplings farmed under different shade conditions contained higher species-characteristic leaf polyphenolic concentrations with increasing light while most alkaloids increased with the shade. When analyzed the following year, higenamine, boldine, isocorydine and N-methyllaurotetanine increased. The principal components of the leaf essential oils from the wild populations were p-cymene, ascaridole and 1,8-cineole, while in the farmed trees ascaridole was replaced by its precursor α-terpinene as the second most abundant constituent. Although multiple factors may affect the concentration of secondary metabolites and geographic provenances with its attending differences in sunlight and rainfall has been suggested as one of these, the present work shows that latitude by itself cannot explain differences that have a clear impact on quality from the medicinal standpoint. © 2023 Elsevier GmbH